Manfaat Literasi Al-Qur’an dalam Pembentukan Karakter Murid-Murid di TPQ dan RTQ Baitul Qur’an Kota Bukittinggi - Zul Efendi (STIKes Ibnu Sina Ajibarang, 2025)
Qur’anic literacy plays a strategic role in shaping students’ character in Islamic educational institutions, particularly at TPQ and RTQ. This study aims to analyze how Qur’anic literacy contributes to strengthening children’s moral, spiritual, and social values in both formal and non-formal educational contexts. Employing a qualitative approach through an extensive literature review, the research synthesizes findings from previous studies on Qur’an-based character education, emphasizing the multidimensional nature of literacy that goes beyond reading and memorization. Qur’anic literacy encompasses understanding, internalizing, and applying Qur’anic teachings in daily behavior and decision-making processes. The results indicate that several interrelated factors influence this process, including habituation through regular practice, exemplary role models provided by parents, teachers, and community leaders, as well as the role of the social environment in reinforcing values. Furthermore, constructive implementation of rewards and sanctions is found to be effective in sustaining children’s motivation and discipline. Early habituation of reading, memorizing, and reflecting on the Qur’an has been proven to nurture positive traits such as responsibility, honesty, empathy, and social awareness. The study highlights that Qur’anic literacy is not only a pedagogical tool but also a holistic instrument of character formation that aligns spiritual values with modern educational challenges. These findings affirm the necessity of optimizing Qur’anic literacy programs through synergy among families, schools, and communities, ensuring that children grow into religious, virtuous, and resilient individuals. Ultimately, Qur’anic literacy serves as a foundation for building a generation that is intellectually capable, spiritually grounded, and socially responsible in contributing positively to society and addressing global challenges.